2018
DOI: 10.1097/opx.0000000000001246
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Item Banks for Measuring Quality of Life in Refractive Error

Abstract: We identified the content of two different sets of item banks to comprehensively measure the impact of refractive error on quality of life for people in Australia and Nepal, which may be applicable to high-income country settings and low- and middle-income country settings, respectively. Future work aims to develop computer-adaptive testing system to administer the item banks, resulting in useful measurement tools for researchers, clinicians, and policy planners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Additionally, clinical, demographic, and socio-economic characteristics influence QOL and therefore results vary between populations and groups. 73,75 Despite their limitations, existing PROMs have proven valuable in evaluating QOL impacts of myopia and demonstrate that the impact of myopia on QOL is significant. The detrimental impacts of myopia have been observed in diverse aspects of daily living, including activity limitation, economic wellbeing, emotional well-being, symptoms, and social wellbeing.…”
Section: Patient-reported Outcomes -Quality Of Life and Myopiamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, clinical, demographic, and socio-economic characteristics influence QOL and therefore results vary between populations and groups. 73,75 Despite their limitations, existing PROMs have proven valuable in evaluating QOL impacts of myopia and demonstrate that the impact of myopia on QOL is significant. The detrimental impacts of myopia have been observed in diverse aspects of daily living, including activity limitation, economic wellbeing, emotional well-being, symptoms, and social wellbeing.…”
Section: Patient-reported Outcomes -Quality Of Life and Myopiamentioning
confidence: 99%
“…The detrimental impacts of myopia have been observed in diverse aspects of daily living, including activity limitation, economic wellbeing, emotional well-being, symptoms, and social wellbeing. 66,73,[75][76][77] Generally, poorer QOL has been demonstrated for uncorrected refractive error/poor vision and high myopia as well as with complications associated with myopia. In a group of 16-year-old patients, myopia was an independent risk factor for poorer QOL for both distance and near vision, whereas hyperopia was not associated with any difficulty.…”
Section: Patient-reported Outcomes -Quality Of Life and Myopiamentioning
confidence: 99%
“…[38][39][40][41] Although such technological advances may attempt to satisfy the complexity of presbyopic treatment requirements, the development of age-related conditions such as dry eye may hinder patients' lens-wearing experience in terms of vision and comfort. 42,43 Females are more likely than males to wear contact lenses for presbyopia, owing in part to cosmetic reasons. 39,44 In a survey of 14,690 patients in the UK, women were twice as likely to have a presbyopic contact lens correction, 45 and an Irish study found that 65% of the patients (N=97) undergoing surgical compensation of presbyopia and additional ametropia were female.…”
Section: Contact Lensesmentioning
confidence: 99%
“… 38–41 Although such technological advances may attempt to satisfy the complexity of presbyopic treatment requirements, the development of age-related conditions such as dry eye may hinder patients’ lens-wearing experience in terms of vision and comfort. 42 , 43 …”
Section: Presbyopic Treatment Optionsmentioning
confidence: 99%
“…The authors reported that while the NEI Refractive Error Quality of Life instrument (NEI-RQL) was the most frequently used, it did not provide valid measurement, whereas a number of other instruments, including the Quality of Vision, Near Activity Visual Questionnaire, and Quality of Life questionnaire (QIRC) had been constructed using Rasch analysis and were suited to measurement of visual symptoms, activity limitations, and QoL, respectively. They subsequently developed a pool of refractive error items from patient groups in Australia (n=337 items) and Nepal (n=308 items), spanning 12 QoL domains and are working to develop a CAT system suitable for use in both high- and low-income country settings 88. An RCT using PROMs as the primary outcome measure to compare ready-made spectacles and custom-made spectacles for the correction of refractive error in adults in India found that both result in comparable patient satisfaction and large gains in visual function and QoL, with the custom-made spectacles achieving a small but statistically significant higher QoL outcome 89…”
Section: Impact Of Proms By Ophthalmic Subspecialtymentioning
confidence: 99%